How Indonesian Students View Code-Mixing in Daily Conversations - Nugraha, Indra; Jaelani, Alan; Sukma, Bayu Permana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
Multilingualism in Indonesia refers to local or regional languages as the first or mother tongue, Bahasa Indonesia as the second or official language, and foreign languages in which English is the most spoken foreign language in Indonesia. Such a condition may bring us to code-mixing. Code-mixing is using more than one language or language variety in conversation. To some linguists, code-mixing is perceived as a negative phenomenon for several reasons, such as reducing the sense of necessity to use the 'original' language of the speakers. However, this view might only be found among the older generation. How about the younger generation's perception of the code-mixing phenomenon? This study explores the students' perception of code-mixing in daily conversations. The study used a questionnaire-based research method and involved 83 respondents from majors such as English education, Islamic broadcasting communication, and management aged 18-23. The results show that 73.5% of the respondents consider code-mixing a normal phenomenon in daily conversations. Furthermore, 51.8% of the respondents perceive code-mixing as usual while engaging in conversation, 41% as a positive phenomenon due to bilingual capacity, and only 7.2% perceive code-mixing as a negative one regarding disrespectful reasons to Bahasa Indonesia.